Experimental Study of a Web Slipping on Rollers with Holes under Considering Air Temperature - Puttha Jeenkour (Japanese Society of Tribologists, 2018)
This article aims to experimentally study a slipping thin film on a roller of varying configurations. The investigated options include a smooth roller, a roller with a v-grooved surface, and a roller with holes under varying web tension and air temperature. The slippage phenomenon is a serious problem in the manufacturing of thin films, because it prevents continuous production and associated costs will increase. Therefore, the roller should be modified in order to mitigate the effects of slippage. To study the modified roller surface , an experimental apparatus was designed. The driving roller was modified to add holes, and an acrylic chamber covered the experimental apparatus to control air temperature. The specific web examined in this study was Polyethylene terephthalate (PET). The experiment showed that the roller with holes is an effective alternative for reducing slippage of web. The air temperature also greatly affected slippage of the web. When the air temperature increased above the ambient temperature of 60 degrees celsius, the operating web speed needed to be decreased in order to eliminate slipping.